PEMANFAATAN TUMBUHAN UNTUK PAKAIAN TRADISIONAL SUKU MEE DI KAMPUNG WIYOGEI DISTRIK KAMUU UTARA KABUPATEN DOGIYAI PAPUA - Benyamin Degei; Konstantina M.B. Kameubun; Alfred A. Antoh (NOVAE GUINEA Jurnal Biologi, 2023)
ABSTRAK        Kampung wiyogei adalah kampung yang terletak di Distrik Kamuu Utara, kabupaten Dogiyai, Provinsi Papua. Pakaian tradisional untuk laki-laki dan perempuan Suku Mee di Kampung Wiyogei menggunakan Tumbuh-tumbuhan. Penelitian ini bertujuan untuk mengetahui jenis-jenis tumbuhan, pemanfaatannya dan upaya pelestarian tumbuhan untuk pakaian tradisional suku Mee di kampung Wiyogei, Distrik Kamuu Utara, Kabupaten Dogiyai, Papua. Metode yang digunakan dalam penelitan ini adalah metode observasi, wawancara, dokumentasi dan studi pustaka. Masyarakat di kampung Wiyogei memanfaatkan 13 jenis dari 4 famili tumbuhan untuk pakaian tradisional suku Mee, 12 jenis tumbuhan terdapat di hutan dan 1 jenis tumbuhan yang sudah membudidayakan yaitu buah labu (siceraria lagenaria) untuk pembuatan koteka dan nama ilmiah diperoleh dari hasil identifikasi sampel yang dibuat herbarium di Manokwari. Pelestarian budaya upacara adat yang menggunakan pakaian tradisional masih terus dilakukan bahkan dalam keseharian hidup masyarakat suku Mee di kampung Wiyogei beberapa orang masih menggunakan pakaian tradisional.Kata Kunci : Pemanfaatan, Tumbuhan, Pakaian Tradisional, suku Mee, Wiyogei, Dogiyyai, PapuaABSTRACTWiyogei village is a village located in North Kamuu District, Dogiyai district, Papua Province. Traditional clothing for men and women of the Mee tribe in Wiyogei Village uses plants. This study aims to determine the types of plants, their uses and efforts to preserve plants for traditional clothing of the Mee tribe in Wiyogei village, North Kamuu District, Dogiyai Regency, Papua. The method used for this research is a qualitative descriptive method, through an emic approach and an ethnic approach. This research was conducted in Wiyogei village, North Kamuu District, Dogiyai Regency, Papua. The population in this study is the Wiyogei village community in the North Kamuu district and the plants found in the Wiyogei village. The main sample is the community that is used as knowledge material in the utilization of plant species for traditional clothing of the Mee tribe. Data collection techniques used in this study were observation, interviews, documentation and literature study. The data obtained in this study were analyzed descriptively qualitatively. This study resulted in the following findings: the people in the Wiyogei village used 13 species from 4 plant families for traditional clothing for the Mee tribe, 12 species of plants were found in the forest used for making moge and noken, and 1 plant species that had been cultivated, namely pumpkin (siceraria lagenaria). ) for the manufacture of koteka and the scientific name was obtained from the identification of samples made by the herbarium in Manokwari. Preservation of traditional ceremonial culture using traditional clothing is still being carried out, even in the daily life of the Mee people in Wiyogei village, some people still use traditional clothes.Keywords : Utilization, Plants, Traditional Clothing, Mee tribe, Wiyogei, Dogiyyai, Papua